TAXONOMICALLY SIGNIFICANT COLOR REACTIONS OF BREVIBACTERIUM LINENS - Grecz, Nicholas (1961)
Grecz, Nicholas (University of Chicago, Chicago, Ill.), and Gail M. Dack. Taxonomically significant color reactions of Brevibacterium linens. J. Bacteriol. 82:241–246. 1961.—Brevibacterium linens was observed to give characteristic color reactions with certain bases and acids. An intensive carmine-red color appeared immediately after addition of a drop of 5 n sodium hydroxide, 5 n potassium hydroxide, and saturated barium hydroxide. A light carmine-red was given by lithium hydroxide, and a light orange-red with a milky suspension of calcium hydroxide. No discernible color change was given with weak bases such as ammonium hydroxide, aniline, and pyridine. A characteristic salmon-pink color was produced when B. linens was rubbed with a glass rod in a drop of glacial acetic acid or filter paper; a brick-red color was produced with aniline under these conditions. With syrupy phosphoric acid a green color appeared within 3 to 4 min which turned blue after approximately 3 hr. The blue color was stable for several days. On the basis of these color reactions, B. linens could be distinguished from other microorganisms possessing yellow-orange pigmentation, i.e., Staphylococcus aureus, Staphylococcus epidermidis, Micrococcus flavus, Micrococcus citreus, Mycobacterium phlei, Sarcina lutea. Therefore, these color changes may be used for the identification of B. linens. Original isolates of B. linens from cheese were tested by these spot reactions and all presumptive identifications could be subsequently confirmed by conventional methods. Blue and green colors appeared in all yellow-orange chromogens treated with sulfuric, perchloric, and hydrochloric acids and hence these colors were not specific for B. linens.